Phytochemical and ftir analysis of a mangrove plant - Volkameria inermis L. - P. Shanthi,; U. Thiripura Sundari,; C. Sownthariya,; A. Nisha, (International Journal of Pharma and Bio Sciences, 2020)
Volkameria inermis L. is an important medicinal plant of mangrove region. The main objective of this work was to analyse the bioactive constituents and to identify the functional groups using preliminary phytochemical and FTIR studies. In the present study, finely grounded leaf powder of V. inermis L. was extracted with Hexane, Acetone and Methanol solvents separately. Qualitative and quantitative analysis of various extracts were carried out according to the standard methods. The methanol extract of V. inermis was examined under FTIR spectrophotometer method for identifying the kinds of chemical bonds (functional groups) present in plant powder and the characteristic peaks were recorded. In qualitative analysis, the various leaf extracts of V. inermis showed the presence of active phytochemical constituents, like alkaloids, flavonoids, glycosides, phenol, tannin and steroids and quantification of secondary metabolites showed 14.5mg/g of alkaloid, 67.97mg/g of phenol and 86mg/g of flavonoids. The FTIR spectrum study revealed the presence of many functional groups, such as hydroxyl group, methoxy, methyl ether, aromatic ring, carbonate ion, aliphatic fluoro compound, cyclohexane ring, polysulphides, iodide and bromide compounds. Thus the results of the present study confirms the medicinal potential of V. inermis in various treating system.